Clinical, laboratoy histopathological and ultrastructural study of secondary sjogrens syndrome - Mustafa, Nazih Shaban; Mustafa Al-Ahmad, Basma Ezzat (IIUM Press, International Islamic University Malaysia, 2018)
Sjogren’s syndrome is often referred to as the “great mimicker” because its symptoms often imitate other diseases. It is an autoimmune disease, and a chronic disorder that causes insufficient moisture production in certain glands of the body. It may occur when a person’s normally protective immune system attacks and destroys moisture-producing glands, including salivary (saliva-producing) glands and lacrimal (tear-producing) glands, it also causes vaginal dryness. The lungs, upper respiratory tract, bowel and other organs are less often affected by Sjogren’s syndrome. SS is named after a Swedish Opthalmologist, Henrik Sjogren, (1939) who wrote the classic monograph on the disease in which he emphasized that the eye manifestations are local findings of systemic disorder.Normally, the immune system (the body’s defense system) protects the body from infection and foreign substances such as bacteria and viruses. In auto immune disease, such as Sjogren’s syndrome, the immune system triggers an inflammatory response when there are no foreign substances to fight off. This inflammatory response causes the body’s white blood cells to attack and destroy certain moisture-producing glands. The exact cause for the abnormal immune response in Sjogren’s syndrome is unknown. Some theories suggest that a virus or bacteria may alter the immune system, causing it to attack the glands. Certain people may have a genetic or inherited factor that makes them more3 likely to develop Sjogren’s syndrome.